2019
DOI: 10.1007/s00132-018-03678-2
|View full text |Cite
|
Sign up to set email alerts
|

Repair of osteonecrosis of the femoral head

Abstract: Background Osteonecrosis of the femoral head (ONFH) is a common joint disease and a major cause of morbidity. Objective In this study Cervi cornus Colla (CCC) deproteinized bone scaffolds were designed and three dimensional (3D)-printed for the repair of ONFH in rats. Material and methods The CCC-deproteinized bone scaffolds were 3D-printed using polycaprolactone mixed with the CCC-deproteinized bone powder. The scaffolds were viewed under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…They implanted the scaffold into the femoral head of the mouse model with osteonecrosis of the femoral head (ONFH) to repair osteonecrosis (Figure 3B) and found that the CCC deproteinized bone scaffold significantly reduced femoral head necrosis in rats (Figure 3C). In vitro experiments also showed that osteoblasts aggregated and adhered in the pore structure of the CCC deproteinized bone scaffold, and the CCCdeproteinized bone scaffold enhances the proliferation of osteoblasts (Wang et al, 2019b).…”
Section: Cervi Cornus Collamentioning
confidence: 96%
See 2 more Smart Citations
“…They implanted the scaffold into the femoral head of the mouse model with osteonecrosis of the femoral head (ONFH) to repair osteonecrosis (Figure 3B) and found that the CCC deproteinized bone scaffold significantly reduced femoral head necrosis in rats (Figure 3C). In vitro experiments also showed that osteoblasts aggregated and adhered in the pore structure of the CCC deproteinized bone scaffold, and the CCCdeproteinized bone scaffold enhances the proliferation of osteoblasts (Wang et al, 2019b).…”
Section: Cervi Cornus Collamentioning
confidence: 96%
“…CCC has been used to prevent and treat acute and chronic arthritis, osteoporosis, fractures, hypercholesterolemia, and other diseases (Kim et al, 2013;Li et al, 2014). Wang et al (2019b) processed the proximal pig femur to obtain a deproteinized bone meal. After mixing the deproteinized bone meal with CCC and synthetic organic materials, CCC-deproteinized bone scaffolds were made by 3D printing technology.…”
Section: Cervi Cornus Collamentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have indicated that the cellular outcomes, including cell survival, differentiation and intracellular component synthesis, during the process of cartilage remodelling and repair are influenced by the 3‐dimensional structure and pore size of the material 32 . Accordingly, a scaffold with a pore size ranging from100 to 300 μm demonstrates optimal suitability for promoting cell survival, migration and homing 33 . In the present study, the viability and proliferation ability of the PBMSCs that were seeded on the scaffold with a network structure were found to be higher compared to the control group.…”
Section: Disscussionmentioning
confidence: 99%
“…Their femoral heads had less destruction of chondrocytes along with limited necrosis. In addition, the rats showed no signs of an immune response to the scaffold [ 81 ]. Zhu et al used a novel PLLA/PLGA/PCL scaffold seeded with BMP and combined with low intensity pulsed ultrasound (LIPUS) to observe its effect in repairing ONFH in the rat model.…”
Section: Desired Characteristics Of 3d Scaffoldsmentioning
confidence: 99%